Cash Control Implementation in a Small Building Materials Enterprise: Field Study and Practical Education Program - Selvira Syam; Alcia Ramadhani; Nadhiyah Putri Wahdana; Zulfadli Yusuf; Yustika Jauhari (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2025)
Cash control is a critical component of financial stability, particularly for small enterprises in the building materials sector that manage high volumes of cash transactions. This community engagement activity aims to enhance business owners’ understanding of cash control through a field study and a practical education program. The methods included initial observation, development of educational materials, direct training sessions, and evaluation with follow-up actions. The results indicate a significant improvement in financial management awareness, evidenced by the adoption of daily transaction recording and the separation of personal and business cash. Practice-based education proved effective in building awareness, strengthening basic financial recording skills, and improving cash governance in small enterprises. These findings provide a foundation for designing similar financial literacy programs for the broader MSME sector.